2010
DOI: 10.1074/jbc.m110.123554
|View full text |Cite
|
Sign up to set email alerts
|

Yeast Lipids Can Phase-separate into Micrometer-scale Membrane Domains

Abstract: The lipid raft concept proposes that biological membranes have the potential to form functional domains based on a selective interaction between sphingolipids and sterols. These domains seem to be involved in signal transduction and vesicular sorting of proteins and lipids. Although there is biochemical evidence for lipid raft-dependent protein and lipid sorting in the yeast Saccharomyces cerevisiae, direct evidence for an interaction between yeast sphingolipids and the yeast sterol ergosterol, resulting in me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
77
0
2

Year Published

2011
2011
2022
2022

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 100 publications
(83 citation statements)
references
References 63 publications
(110 reference statements)
4
77
0
2
Order By: Relevance
“…It is clear that a gel/fluid transition that starts at temperatures higher than ϳ42°C was present. The shape of the curve on that temperature range was remarkably similar to a recent study with DPH of the transition temperature of inositol phosphorylceramide (IPC) purified from S. cerevisiae (45). In the same work, it is shown that the melting temperature of IPC is higher than that of a major mammalian sphingolipid (45).…”
Section: S Cerevisiae Plasma Membrane Behavior As a Whole Can Be Difsupporting
confidence: 68%
“…It is clear that a gel/fluid transition that starts at temperatures higher than ϳ42°C was present. The shape of the curve on that temperature range was remarkably similar to a recent study with DPH of the transition temperature of inositol phosphorylceramide (IPC) purified from S. cerevisiae (45). In the same work, it is shown that the melting temperature of IPC is higher than that of a major mammalian sphingolipid (45).…”
Section: S Cerevisiae Plasma Membrane Behavior As a Whole Can Be Difsupporting
confidence: 68%
“…Simulation of lipid bilayers comprising common sphingomyelins showed that increasing acyl chain length enhances bilayer thickness and lipid packing but reduces lateral diffusion because of acyl chain interdigitations (Niemelä et al, 2006). Impairment of yeast fatty acid elongation leading to reduced C26-sphingolipid levels decreased lipid packing and membrane order in yeast cell but also prevented liquid ordered phase separation in model membranes from total lipid extracts (Klose et al, 2010). Such structural properties of the acyl chains of sphingolipids could infer specific membrane features like vesicular mobility or fusions that could define some endosomal populations and PM subdomains.…”
Section: Discussionmentioning
confidence: 99%
“…BODIPY-cholesterol has many attractive photophysical properties, such as a high fl uorescence quantum yield, high photostability, and insensitivity to pH and polarity ( 13,(25)(26)(27). It partitions into the liquid-disordered and liquid-ordered phases of model bilayer membranes and cell membranes ( 28 ), with a preference for the liquid-ordered phase in giant unilamellar vesicles ( 29 ). BODIPY-cholesterol has been used for live-cell monitoring of cholesterol traffi cking ( 30 ) and for analysis of the kinetics of transfer of self-quenched BODIPY-cholesterol from donor to acceptor vesicles in the presence of StAR protein ( 31 ).…”
Section: Discussionmentioning
confidence: 99%